Reassessing the Dream-Vision of the Vision of Amram (4Q543–547) - Jurgens, Blake A. (2014)
The Vision of Amram has been interpreted by many as a prime example of dualistic theology, portraying two ostensibly antagonistic figures contending over having authority over the person of Amram. This study pushes against this interpretation and instead recontextualizes Amram's otherworldly experience with a greater emphasis on both the surrounding episodes of the composition as well as the identification of Melchizedek—a figure with intricate ties to priestly legitimacy—as the oppositionary figure up against the ominous Melchiresha in the dream-vision. In this fashion, this study concludes that the dream-vision of Amram represents an either–or choice in which the protagonist is required to choose between a legitimate or a corrupted priesthood. Moreover, Amram's vision thus stands as a metaphorical depiction of an underlying historical conflict between two priestly groups, an image which the latter Qumranites certainly reappropriated to their own historical situation.
Keywords: priestly inheritance; endogamy; Melchiresha; Melchizedek; Vision of Amram